2016
DOI: 10.1055/s-0036-1592271
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bronchiectasis in the elderly

Abstract: Introduction. Although bronchiectasis particularly affects people 65 years of age, data describing clinical characteristics of the disease in this population are lacking. This study aimed at evaluating bronchiectasis features in older adults and elderly, along with their clinical outcomes.Methods. This was a secondary analysis of six European databases of prospectively enrolled adult outpatients with bronchiectasis. Bronchiectasis characteristics were compared across three study groups: younger adults (18-65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The prevalence of bronchiectasis increased with patient age in previous studies [1,2]. Likewise, we observed that 50% of patients in the bronchiectasis cohort were over 65 years old [26]. Increased age is considered a risk factor for bronchiectasis [27].…”
Section: Discussionsupporting
confidence: 60%
“…The prevalence of bronchiectasis increased with patient age in previous studies [1,2]. Likewise, we observed that 50% of patients in the bronchiectasis cohort were over 65 years old [26]. Increased age is considered a risk factor for bronchiectasis [27].…”
Section: Discussionsupporting
confidence: 60%
“…The study cohort is typical of the older population (⩾65 year old) in the USA, which includes ∼75% all bronchiectasis patients, in contrast to Europe where 50% of all bronchiectasis patients are ⩾65 years old [30,31]. The proportion of female patients in each treatment group (67% ICS and 73% macrolide) was higher than reported in the UK (58%), but similar to the overall population of adults with bronchiectasis in the USA (67%) [2,30].…”
Section: Discussionmentioning
confidence: 75%
“…Studies reporting SGRQ total scores were able to discriminate based on demographics (Bellelli et al, 2016, disease severity (Chalmers et al, 2014, Eshed et al, 2007, Martinez Garcia et al, 2005, exacerbations (Altenburg et al, 2016, Murray et al, 2009a, Martinez Garcia et al, 2005, Guan et al, 2014, Brown et al, 2019, bacteriology (Chalmers et al, 2014, Martinez Garcia et al, 2005, Hill et al, 2015a, Araujo et al, 2018, Brown et al, 2019, Basavaraj et al, 2019, sputum volume (Chan et al, 2002, Martinez Garcia et al, 2005, dyspnoea (Chalmers et al, 2014, chronic rhinosinusitis (Guilemany et al, 2009), sleep quality (Gao et al, 2014a), anxiety and depression (Gao et al, 2018) and exercise capacity (Guan et al, 2015a). Studies reporting SGRQ domain scores were able to discriminate based on disease severity (McDonnell et al, 2016, Eshed et al, 2007, exacerbations (Murray et al, 2009a, Guan et al, 2015b, bacteriology (Wilson et al, 1997a), sputum volume (Chan et al, 2002), chronic rhinosinusitis (Guilemany et al, 2009), wheeze (Wilson et al, 1997a), sleep quality (Gao et al, 2014a), and exercise capacity (Guan et al, 2015a).…”
Section: Respiratory Specific Hrqol Questionnairesmentioning
confidence: 99%